Sodium ion battery positive electrode material precursor and its preparation method and application
By combining the NASICON type material precursor with the positive electrode material precursor and covering the NASICON type material through wet coating method, the problem of low capacity retention rate of the positive electrode material of sodium ion battery during long cycles is solved, and high efficiency is achieved Sodium ion migration and electrochemical performance improve, while reducing production costs.
Patent Information
- Application Number
- CN202311067811.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-23
AI Technical Summary
When the sodium ion battery layered oxide positive electrode material achieves reversible sodium ions de-insertion and embedding, it faces complex structural evolution, affecting its capacity retention rate during long cycles, and the existing coating methods are complex and costly.
The NASICON type material precursor is combined with the positive electrode material precursor, and the NASICON type material precursor is uniformly coated on the surface of the positive electrode material precursor through wet coating to form the positive electrode material precursor of sodium ion battery, and sintering is obtained. Coated sodium ion battery positive electrode material.
It significantly improves the cycle stability and rate performance of the positive electrode material of sodium ion battery, reduces production costs, and improves the sodium ion migration efficiency.
Smart Images

Figure CN117049610B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sodium ion battery positive electrode material precursor and a preparation method and application thereof. Background Art
[0002] Lithium, sodium, and potassium all belong to the alkali metal elements of Group IA of the periodic table. They have similar physical and chemical properties and can theoretically be used as metal ion carriers for secondary batteries. Among them, lithium has a smaller ion radius, a higher standard potential, and a much higher specific capacity than sodium and potassium, so it has been used earlier and more widely in secondary batteries. However, the global reserves of lithium resources are limited. With the substantial increase in demand for batteries due to the development of new energy vehicles, bottlenecks on the resource side have gradually emerged, and the high cost has limited the large-scale application of lithium-ion batteries.
[0003] Sodium resources are very abundant, with an abundance of 2.64% in the earth's crust, 440 times that of lithium resources. Sodium resources are widely distributed and easy to extract. Sodium has emerged as a substitute for lithium and has received more and more attention in the battery field. After development in recent years, the comprehensive performance and demonstration applications of sodium-ion batteries have achieved remarkable results. As a beneficial supplement to lithium-ion batteries, sodium-ion batteries will achieve great development in the fields of large-scale energy storage and micro electric vehicles. Electrode materials with high specific energy will continue to be the goal that people are striving for.
[0004] The key technology of sodium-ion batteries is mainly material technology. The key to having long-life batteries is to develop materials with high stability. Due to the difference in ion properties, it is not appropriate to directly replace the lithium in the electrode material of lithium-ion batteries with sodium. Therefore, finding electrode materials suitable for sodium-ion batteries is the key to the practical application of lithium-ion batteries.
[0005] In the past decade, cathode materials, as one of the key components of sodium-ion batteries, have been widely studied, such as layered oxides, polyanion compounds, Prussian blue compounds, organic compounds, etc. x TMO2 (TM is generally a transition metal, x≤1) is similar to the successfully commercialized lithium-ion layered oxides, and has the advantages of high specific capacity, simple preparation, high compaction density, and adjustable voltage range, and has been extensively studied. However, when the sodium-ion layered oxide positive electrode material achieves more reversible extraction / embedding of sodium ions, the system faces complex structural evolution, which seriously affects its capacity retention rate during long cycles.
[0006] Although doping or substitution of transition metal sites can significantly inhibit phase transition, inhibit the migration of transition metal ions and improve the chemical and electrochemical stability of de-sodiumized materials, it will inevitably reduce the content of redox couples in the system and thus affect the energy density of the system. In addition, too little doping ion content will not be enough to stabilize the structure of the layered oxide material. In addition, K can be doped into the sodium ion site to + Mg 2+ , Ca 2+ or Zn 2+ , playing a supporting role, thereby effectively alleviating the electrostatic repulsion between the sodium layers OO and inhibiting the occurrence of phase transition, but the doping amount is difficult to increase, and it will also sacrifice the energy density of the system.
[0007] Coating modification is widely used in lithium-ion layered oxide cathode materials and has significant effects, but research on sodium-ion layered oxides is still relatively rare. This is mainly because the air and water stability of sodium-ion layered oxides is poor, which makes the aqueous solution coating method commonly used in lithium batteries no longer applicable in sodium-ion batteries, and the complex operation process will significantly increase the preparation cost of electrode materials.
[0008] Therefore, it is imperative to develop a simple and effective coating method that can improve the cycling performance of sodium-ion layered oxide materials at higher specific capacities. Summary of the invention
[0009] In view of the above problems existing in the prior art, the object of the present invention is to provide a sodium ion battery positive electrode material precursor and a preparation method and application thereof.
[0010] To achieve the above object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a sodium ion battery positive electrode material precursor, the sodium ion battery positive electrode material precursor comprising a positive electrode material precursor and a NASICON type material precursor;
[0012] The NASICON type material precursor is a substance that is converted into a NASICON type material after calcination.
[0013] It should be noted that, in the "calcination" process of "the NASICON-type material precursor is a substance that is converted into a NASICON-type material after calcination", sodium needs to be added before sintering. For example, the NASICON-type material precursor is mixed with sodium salt and then calcined to obtain a NASICON-type material.
[0014] In the present invention, there is no limitation on the existence form of the positive electrode material precursor and the NASICON type material precursor, and the two may exist in the form of a mixture or in a coated state, for example, the NASICON type material precursor is coated on the surface of the positive electrode material precursor to form the sodium ion battery positive electrode material precursor.
[0015] NASICON-type materials have a conductivity far higher than that of lithium ions, and the NASICON structure is flexible and can accommodate transition metal ions, which can introduce electronic conductivity and store sodium ions, effectively improving the efficiency of sodium ion migration. It is further preferred to coat the NASICON-type material on the surface of the positive electrode material to improve the uniformity of the coating layer, thereby greatly improving the cycle performance and rate performance of the material. At the same time, the present invention solves the problem of poor air and water stability of the coating in the sintering stage of the rear-end positive electrode material by using a common positive electrode material precursor and a NASICON-type material precursor at the precursor end.
[0016] The sodium ion battery positive electrode material precursor of the present invention is used to prepare the sodium ion battery positive electrode material, which can effectively improve the cycle stability and rate performance of the sodium ion battery and has the advantage of low cost.
[0017] As a preferred embodiment, a NASICON type material precursor is coated on the surface of a positive electrode material precursor to form the sodium ion battery positive electrode material precursor. In the positive electrode material prepared using the sodium ion battery positive electrode material precursor, a layer of NASICON type material is coated on the surface of the sodium battery positive electrode material, which can better improve the sodium ion migration efficiency.
[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0019] Preferably, the cathode material precursor is a layered oxide cathode material precursor, preferably a quaternary layered oxide cathode material precursor.
[0020] Preferably, the chemical formula of the quaternary layered oxide positive electrode material is Ni a Fe b Cu c Mn d(OH)2, where 0 < a ≤ 0.4, 0 < b ≤ 0.4, 0 < c ≤ 0.3, 0 < d ≤ 0.6, and a + b + c + d = 1. Exemplarily, a can be 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4, etc., b can be 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4, etc., c can be 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, or 0.3, etc., d can be 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, or 0.6, etc. This quaternary layered oxide cathode material is simply referred to as nickel-iron-copper-manganese quaternary precursor.
[0021] Due to the poor air and water stability of the layered oxide sodium-ion cathode material, the process of sintering and coating in the cathode stage is extremely complex. In the present invention, coating is carried out at the precursor stage, which can reduce the complexity of subsequent processes and lower production costs.
[0022] Preferably, the NASICON-type material is NaMg x Zr y Ti 1-x-y (PO4)3, where 0.1 ≤ x ≤ 0.3, 0.1 ≤ y ≤ 0.3. x can be, for example, 0.1, 0.15, 0.2, 0.25, or 0.3, etc., and y can be, for example, 0.1, 0.15, 0.2, 0.25, or 0.3, etc.
[0023] In a second aspect, the present invention provides a method for preparing a precursor of a sodium-ion battery cathode material as described in the first aspect, the method comprising the following steps:
[0024] (1) Prepare the raw materials of the NASICON-type material precursor into aqueous solutions respectively, and add them in a co-current manner with an ammonia aqueous solution to a reaction system containing the cathode material precursor for reaction to obtain the precursor of the sodium-ion battery cathode material.
[0025] The present invention uses a wet coating method to uniformly coat a precursor with a NASICON structure on the surface of a cathode material precursor (such as a nickel-iron-copper-manganese quaternary precursor). The cathode material is prepared therefrom, and a cathode material for a sodium-ion battery coated with a NASICON-type material can be obtained by one-step sintering. The NASICON-type material has a stable structural framework, high electronic conductivity, and good thermal stability, which can effectively improve the sodium ion migration efficiency and thus improve the electrochemical performance of the cathode material for a sodium-ion battery.
[0026] As a preferred technical solution of the preparation method of the cathode material precursor for a sodium-ion battery described in the present invention, the raw materials of the NASICON-type material precursor include phosphoric acid, a magnesium salt, a zirconium salt, and a titanium salt.
[0027] The present invention does not limit the specific types of the magnesium salt, the zirconium salt, and the titanium salt. Exemplarily but not restrictively, the magnesium salt can be magnesium sulfate, the zirconium salt can be zirconium sulfate, and the titanium salt can be titanium oxysulfate.
[0028] Preferably, the concentration of the aqueous solution in step (1) is independently 0.1 mol / L to 1 mol / L, such as 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, or 1 mol / L, etc.
[0029] Preferably, the feeding rate of the aqueous solution prepared with phosphoric acid is 30 L / h to 90 L / h, such as 30 L / h, 35 L / h, 38 L / h, 40 L / h, 43 L / h, 46 L / h, 48 L / h, 50 L / h, 55 L / h, 60 L / h, 65 L / h, 70 L / h, 75 L / h, 80 L / h, 85 L / h, or 90 L / h, etc.
[0030] Preferably, the feeding rate of the aqueous solution prepared with the magnesium salt is 10 L / h to 30 L / h, such as 10 L / h, 15 L / h, 18 L / h, 20 L / h, 23 L / h, 26 L / h, 28 L / h, or 30 L / h, etc.
[0031] Preferably, the feeding rate of the aqueous solution prepared with the zirconium salt is 10 L / h to 30 L / h, such as 10 L / h, 15 L / h, 18 L / h, 20 L / h, 23 L / h, 26 L / h, 28 L / h, or 30 L / h, etc.
[0032] Preferably, the feeding rate of the aqueous solution prepared with the titanium salt is 50 L / h to 200 L / h, such as 50 L / h, 80 L / h, 100 L / h, 120 L / h, 140 L / h, 160 L / h, 180 L / h, or 200 L / h, etc.
[0033] Preferably, the mass concentration of the ammonia water solution is 15% to 30%, such as 15%, 16%, 18%, 20%, 22%, 23%, 25%, 27%, 28% or 30%, etc.
[0034] Preferably, the feeding rate of the ammonia water solution is 5 L / h to 30 L / h, such as 5 L / h, 10 L / h, 15 L / h, 18 L / h, 20 L / h, 23 L / h, 26 L / h, 28 L / h or 30 L / h, etc.
[0035] Preferably, the time for co-current addition is 1 h to 15 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc.
[0036] Preferably, the precursor of the positive electrode material is a layered oxide positive electrode material, preferably a quaternary layered oxide positive electrode material.
[0037] Due to the poor air and water stability of the layered oxide sodium-ion positive electrode material, the process of sintering and coating in the positive electrode stage is extremely complex. In the present invention, wet coating is carried out at the precursor end, which can greatly improve the uniformity of the coating layer, reduce the complexity of the subsequent process, and reduce the production cost.
[0038] Preferably, the reaction system containing the precursor of the positive electrode material is: the reaction system for co-precipitating the precursor of the positive electrode material.
[0039] The present invention does not specifically limit the preparation method of the precursor of the positive electrode material, and those skilled in the art can refer to the methods disclosed in the prior art for preparation.
[0040] Taking the quaternary layered oxide positive electrode material with the chemical formula Ni a Fe b Cu c Mn d (OH)2 (where 0 < a ≤ 0.4, 0 < b ≤ 0.4, 0 < c ≤ 0.3, 0 < d ≤ 0.6, and a + b + c + d = 1) as an example, an exemplary preparation method of the precursor of the sodium-ion battery positive electrode material is provided, including the following steps:
[0041] Step 1: Prepare a nickel-iron-copper-manganese metal salt solution A with a total metal ion concentration of 0.5 mol / L to 2.5 mol / L by mixing soluble nickel salt, soluble iron salt, soluble copper salt and soluble manganese salt in a certain proportion;
[0042] Prepare a complexing agent solution B with a concentration of 0.05 mol / L to 0.1 mol / L;
[0043] Use industrial liquid caustic soda as the precipitant C;
[0044] Step 2: Add a certain amount of pure water, liquid alkali and complexing agent to the reactor to prepare the bottom liquid, continue to introduce nitrogen for protection, add the mixed solution A, complexing agent solution B and precipitant C to the reactor at a certain flow rate, react at 30°C to 60°C, maintain the reaction pH at 8.5 to 12, the complexing agent concentration at 0.01 mol / L to 0.1 mol / L, the stirring speed at 200 rpm to 500 rpm, suspend the feeding after a period of reaction, and obtain a nickel-iron-manganese-copper hydroxide precursor;
[0045] Step 3: Phosphoric acid, magnesium salt, zirconium salt and titanium salt are respectively prepared into aqueous solutions of a certain concentration, and are continuously fed with an ammonia solution at a certain flow rate for a period of time to obtain a coated sodium ion battery positive electrode material precursor.
[0046] In one embodiment, in step 1, the soluble nickel salt includes but is not limited to at least one of nickel sulfate, nickel chloride and nickel nitrate.
[0047] In one embodiment, in step 1, the soluble iron salt includes but is not limited to at least one of ferrous sulfate, ferrous chloride and ferrous nitrate.
[0048] In one embodiment, in step 1, the soluble copper salt includes but is not limited to at least one of copper sulfate, copper chloride and copper nitrate.
[0049] In one embodiment, in step 1, the soluble manganese salt includes but is not limited to at least one of manganese sulfate, manganese chloride and manganese nitrate.
[0050] In one embodiment, in step 1, the complexing agent in the complexing agent solution B is selected from at least one of ammonia water, EDTA, ammonium bicarbonate and sodium pyrophosphate.
[0051] In one embodiment, in step 1, the concentration of the industrial liquid caustic soda is 32%.
[0052] In one embodiment, in step 2, the volume of the reactor is 8000L.
[0053] In a third aspect, the present invention provides a sodium ion battery positive electrode material, which is prepared using the sodium ion battery positive electrode material precursor described in the first aspect, and the sodium ion battery positive electrode material includes a positive electrode material core and a NASICON type material coated on the surface of the positive electrode material core.
[0054] Preferably, based on the total mass of the sodium ion battery positive electrode material as 100%, the mass content of the NASICON type material is 1% to 10%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 10%, etc.
[0055] In a fourth aspect, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described in the third aspect, the method comprising the following steps:
[0056] The sodium ion battery positive electrode material precursor and a sodium source are mixed and calcined to obtain the sodium ion battery positive electrode material.
[0057] The present invention does not specifically limit the type of the sodium source, and it may be sodium carbonate, for example.
[0058] Preferably, the calcination temperature is 800°C to 1000°C, for example, 800°C, 825°C, 850°C, 870°C, 880°C, 900°C, 950°C or 1000°C.
[0059] Preferably, the calcination time is 12 h to 20 h, for example, 12 h, 13 h, 14 h, 15 h, 16 h, 18 h or 20 h.
[0060] In a fifth aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the third aspect.
[0061] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] (1) The present invention uses a NASICON-type material precursor and a positive electrode material precursor in combination to form a positive electrode material precursor for a sodium ion battery, which effectively improves the sodium ion migration efficiency and sodium storage performance. It is further preferred to coat the NASICON-type material on the surface of the positive electrode material, thereby improving the uniformity of the coating layer, thereby greatly improving the material's cycle performance and rate performance. At the same time, the present invention solves the problem of poor air and water stability of the coating in the rear-end positive electrode material sintering stage by using an ordinary positive electrode material precursor and a NASICON-type material precursor in combination at the precursor end, thereby reducing the complexity of the subsequent process and reducing production costs.
[0064] (2) The sodium ion battery positive electrode material precursor described in the present invention is used to prepare the sodium ion battery positive electrode material, which can effectively improve the cycle stability and rate performance of the sodium ion battery. The rate performance is above 90%, and the capacity retention rate after 500 cycles is above 91%. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a SEM image of the coated sodium ion battery positive electrode material precursor in Example 1. DETAILED DESCRIPTION
[0066] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0067] In the embodiment of the present invention, the positive electrode material precursor is Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 is used as an example and is not limited to this chemical formula. Other cathode material precursors commonly used in the art are also applicable to the present invention.
[0068] Example 1
[0069] This embodiment provides a sodium ion battery positive electrode material precursor, including a positive electrode material precursor and a NASICON type material precursor; the NASICON type material precursor is a substance converted into a NASICON type material after calcination. The positive electrode material precursor is a quaternary layered oxide positive electrode material precursor, the chemical formula of which is Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 (denoted as NFCM precursor), the chemical formula of NASICON type material is NaMg 0.2 Zr 0.2 Ti 1.6 (PO4)3.
[0070] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material precursor, comprising the following steps:
[0071] Step 1: nickel sulfate, ferrous sulfate, copper sulfate, and manganese sulfate are prepared in a metal molar ratio of 1:1:1:1 to prepare a nickel-iron-copper-manganese metal salt solution A having a total metal ion concentration of 1 mol / L;
[0072] Prepare EDTA solution with a concentration of 0.05 mol / L as complexing agent B;
[0073] 32% industrial liquid alkali is used as precipitant C.
[0074] Step 2: Add 6000L of pure water to an 8000L reactor, and add liquid alkali and complexing agent EDTA to prepare the base solution to pH 11.6, with an EDTA concentration of 0.01mol / L. Heat to 38°C and continue to introduce nitrogen for protection. Add the mixed solution A, complexing agent B, and precipitant C to the reactor at a flow rate of 400L / h, 100L / h, and 130L / h, respectively, to maintain the reaction pH at 11.6, the complexing agent concentration at 0.01mol / L, and the stirring speed at 500rpm. After 50h of reaction, stop feeding to obtain Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 precursor.
[0075] Step 3: Phosphoric acid, magnesium sulfate, zirconium sulfate and titanyl sulfate are respectively prepared into 0.5 mol / L aqueous solutions, and 17% ammonia aqueous solution is continuously fed at 60 L / h, 20 L / h, 20 L / h, 160 L / h, and 30 L / h for 1 hour to obtain a coated sodium ion battery positive electrode material precursor.
[0076] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0077] The coated sodium ion battery cathode material precursor and sodium carbonate are mixed evenly, and calcined at 800° C. for 20 h to obtain a sodium ion battery cathode material, wherein the sodium ion battery cathode material comprises NFCM1111 quaternary layered oxide cathode material (chemical formula: NaNi 0.25 Fe 0.25 Cu 0.25 Mn 0.25 O2) and NaMg coated on its surface 0.2 Zr 0.2 Ti 1.6 (PO4)3. Taking the total mass of the positive electrode material of sodium ion battery as 100%, NaMg 0.2 Zr 0.2 Ti 1.6 The mass content of (PO4)3 is 2%.
[0078] Figure 1 This is the SEM image of the coated precursor. It can be seen from the figure that the NASICON material precursor is evenly coated on the NFCM precursor.
[0079] Example 2
[0080] This embodiment provides a sodium ion battery positive electrode material precursor, including a positive electrode material precursor and a NASICON type material precursor; the NASICON type material precursor is a substance converted into a NASICON type material after calcination. The positive electrode material precursor is a quaternary layered oxide positive electrode material precursor, the chemical formula of which is Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2, the chemical formula of NASICON type material is NaMg 0.2 Zr 0.2 Ti 1.6 (PO4)3.
[0081] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material precursor, comprising the following steps:
[0082] Step 1: nickel sulfate, ferrous sulfate, copper sulfate, and manganese sulfate are prepared in a metal molar ratio of 1:1:1:1 to prepare a nickel-iron-copper-manganese metal salt solution A with a total metal ion concentration of 2 mol / L;
[0083] Prepare 0.1 mol / L EDTA solution as complexing agent B;
[0084] 32% industrial liquid alkali is used as precipitant C.
[0085] Step 2: Add 6000L pure water to the 8000L reactor, add liquid alkali and complexing agent EDTA to prepare the base solution to pH 11.0, the EDTA concentration is 0.05mol / L, heat to 50°C and continuously introduce nitrogen for protection. Add the mixed solution A, complexing agent B and precipitant C to the reactor at a flow rate of 400L / h, 100L / h and 130L / h respectively, maintain the reaction pH at 11.0, the complexing agent concentration at 0.05mol / L, the stirring speed at 300rpm, and stop feeding after 40h of reaction to obtain Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 precursor.
[0086] Step 3: Phosphoric acid, magnesium sulfate, zirconium sulfate and titanyl sulfate are respectively prepared into 1 mol / L aqueous solutions, and 25% ammonia solution is fed at 30 L / h, 10 L / h, 10 L / h, 100 L / h, and 18 L / h for 10 hours to obtain a coated sodium ion battery positive electrode material precursor.
[0087] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0088] The coated sodium ion battery cathode material precursor and sodium carbonate are mixed evenly, and calcined at 950° C. for 15 h to obtain a sodium ion battery cathode material, wherein the sodium ion battery cathode material comprises NFCM1111 quaternary layered oxide cathode material (chemical formula: NaNi 0.25 Fe 0.25 Cu 0.25 Mn 0.25 O2) and NaMg coated on its surface 0.2 Zr 0.2 Ti 1.6 (PO4)3. Taking the total mass of the positive electrode material of sodium ion battery as 100%, NaMg 0.2 Zr 0.2 Ti 1.6 The mass content of (PO4)3 is 7%.
[0089] Example 3
[0090] This embodiment provides a sodium ion battery positive electrode material precursor, including a positive electrode material precursor and a NASICON type material precursor; the NASICON type material precursor is a substance converted into a NASICON type material after calcination. The positive electrode material precursor is a quaternary layered oxide positive electrode material precursor, the chemical formula of which is Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2, the chemical formula of NASICON type material is NaMg 0.2 Zr 0.2 Ti 1.6 (PO4)3.
[0091] This embodiment also provides a method for preparing the above-mentioned sodium ion battery positive electrode material precursor, comprising the following steps:
[0092] Step 1: nickel sulfate, ferrous sulfate, copper sulfate, and manganese sulfate are prepared in a metal molar ratio of 1:1:1:1 to prepare a nickel-iron-copper-manganese metal salt solution A having a total metal ion concentration of 2.5 mol / L;
[0093] Prepare a sodium pyrophosphate solution with a concentration of 0.08 mol / L as complexing agent B;
[0094] 32% industrial liquid alkali is used as precipitant C.
[0095] Step 2: Add 6000L pure water to an 8000L reactor, add liquid alkali and complexing agent sodium pyrophosphate to prepare the base solution to pH 12.0, the sodium pyrophosphate concentration is 0.07mol / L, heat to 45°C and continuously introduce nitrogen for protection. Add the mixed solution A, complexing agent B, and precipitant C to the reactor at a flow rate of 400L / h, 100L / h, and 130L / h, respectively, maintain the reaction pH at 12.0, the complexing agent concentration at 0.07mol / L, and the stirring speed at 350rpm. After 35h of reaction, stop feeding to obtain Ni 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 precursor.
[0096] Step 3: Phosphoric acid, magnesium sulfate, zirconium sulfate and titanyl sulfate are respectively prepared into 0.6 mol / L aqueous solutions, and 20% ammonia solution is continuously fed at 45 L / h, 15 L / h, 15 L / h, 140 L / h and 20 L / h for 8 hours to obtain a coated sodium ion battery positive electrode material precursor.
[0097] This embodiment also provides a sodium ion battery positive electrode material, and the preparation method thereof comprises the following steps:
[0098] The coated sodium ion battery cathode material precursor and sodium carbonate are mixed evenly, and calcined at 900° C. for 17 h to obtain a sodium ion battery cathode material, wherein the sodium ion battery cathode material comprises NFCM1111 quaternary layered oxide cathode material (chemical formula: NaNi 0.25 Fe 0.25 Cu 0.25 Mn 0.25 O2) and NaMg coated on its surface 0.2 Zr 0.2 Ti 1.6 (PO4)3. Taking the total mass of the positive electrode material of sodium ion battery as 100%, NaMg 0.2 Zr 0.2 Ti 1.6 The mass content of (PO4)3 is 10%.
[0099] Example 4
[0100] The difference from Example 1 is that the preparation parameters are adjusted so that the total mass of the positive electrode material of the sodium ion battery is 100%, NaMg 0.2 Zr 0.2 Ti 1.6 The mass content of (PO4)3 is 0.5%.
[0101] Example 5
[0102] The difference from Example 1 is that the preparation parameters are adjusted so that the total mass of the positive electrode material of the sodium ion battery is 100%, NaMg 0.2 Zr 0.2 Ti 1.6 The mass content of (PO4)3 is 10.5%.
[0103] Comparative Example 1
[0104] The difference from Example 1 is that the chemical formula of the outer coating layer is NaMg 0.4 Zr 0.4 Ti 1.0 (PO4)3.
[0105] Comparative Example 2
[0106] The difference from Example 1 is that in the preparation stage of the positive electrode material precursor for the sodium ion battery, step 3 is not performed, but the Ni prepared in step 2 is directly used. 0.25 Fe 0.25 Cu 0.25 Mn 0.25 (OH)2 precursor as a precursor of positive electrode material for sodium ion batteries.
[0107] test:
[0108] 1. Preparation of batteries
[0109] The positive electrode material prepared in each embodiment and comparative example is used to prepare a positive electrode sheet, and the preparation method is as follows:
[0110] The positive electrode material, conductive agent (carbon black) and binder (PVDF) were mixed in a mass ratio of 90:5:5 to prepare a positive electrode slurry, which was then coated on aluminum foil to obtain a positive electrode sheet. Sodium metal was used as the counter electrode, glass fiber was used as the separator, and an organic solution of sodium perchlorate was used as the electrolyte. After assembling a half-cell, the electrochemical performance of the positive electrode material was tested.
[0111] 2. Rate performance test: At 25°C, within the voltage range of 2V to 4.1V, charge and discharge three times at 0.2C to obtain the discharge capacity C0 of the last cycle; then, charge and discharge three times at 1C to obtain the discharge capacity C2 of the last cycle; the ratio of C2 / C0 is the rate performance.
[0112] 3. Cycle performance test: At 25°C, in the voltage range of 2.0V to 4.1V, with 0.5C charge / 0.5C discharge, the cycle performance test was carried out, and the capacity retention rate after 500 cycles was calculated. The formula is as follows: Capacity retention rate = 500th discharge specific capacity / first discharge specific capacity × 100%.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115] serial number Rate performance (%) Capacity retention rate (%) Example 1 95.4 98.3 Example 2 91.7 93.3 Example 3 90.2 91.5 Example 4 96.3 93.2 Example 5 93.8 99.9 Comparative Example 1 87.3 89.2 Comparative Example 2 85.9 79.3
[0116] As can be seen from Table 1, the present invention uses a NASICON type material precursor and a positive electrode material precursor to form a sodium ion battery positive electrode material precursor, which effectively improves the sodium ion migration efficiency and sodium storage performance. It is further preferred to coat the NASICON type material on the surface of the positive electrode material to improve the uniformity of the coating layer, thereby greatly improving the material's cycle performance and rate performance.
[0117] Comparing Example 1 with Examples 4-5, it can be seen that the NaMg 0.2 Zr 0.2 Ti 1.6 There is an optimal range for the coating amount of (PO)3. Less than 1% has a negative impact on the capacity retention rate, and more than 10% has a negative impact on the rate performance.
[0118] By comparing Example 1 and Comparative Example 1, it can be seen that the composition of the outer coating layer will also affect the electrochemical performance. The coating layer can improve the interface between the material and the electrolyte, reduce side reactions, and the NASICON material can effectively improve the sodium ion migration efficiency.
[0119] By comparing Example 1 with Comparative Example 2, it can be seen that the present invention uses a NASICON type material precursor and a positive electrode material precursor to form a sodium ion battery positive electrode material precursor, which effectively improves the sodium ion migration efficiency and sodium storage performance. It is further preferred to coat the NASICON type material on the surface of the positive electrode material to improve the uniformity of the coating layer, thereby greatly improving the cycle performance and rate performance of the material.
[0120] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion battery cathode material precursor, characterized in that: The sodium ion battery positive electrode material precursor comprises a positive electrode material precursor and a NASICON type material precursor; the NASICON type material precursor is coated on the surface of the positive electrode material precursor; The NASICON type material precursor is a substance that is converted into a NASICON type material after calcination; The cathode material precursor is a quaternary layered oxide cathode material precursor; the chemical formula of the quaternary layered oxide cathode material is Ni a Fe b Cu c Mn d (OH)2, where 0 < a ≤ 0.4, 0 < b ≤ 0.4, 0 < c ≤ 0.3, 0 < d ≤ 0.6, and a + b + c + d = 1; The NASICON type material is NaMg x Zr y Ti 1-x-y (PO4)3, where 0.1≤x≤0.3, 0.1≤y≤0.3; The sodium ion battery positive electrode material precursor is prepared by the following method, which comprises the following steps: The raw materials of the NASICON type material precursor are respectively prepared into aqueous solutions, and added into the reaction system containing the positive electrode material precursor in parallel with the ammonia solution to react, so as to obtain the positive electrode material precursor of the sodium ion battery.
2. A method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The method comprises the following steps: The raw materials of the NASICON type material precursor are respectively prepared into aqueous solutions, and added into the reaction system containing the positive electrode material precursor in parallel with the ammonia solution to react, so as to obtain the positive electrode material precursor of the sodium ion battery.
3. The method according to claim 2, characterized in that The raw materials of the NASICON type material precursor include phosphoric acid, magnesium salt, zirconium salt and titanium salt.
4. The method according to claim 2, characterized in that: The concentration of the aqueous solution in step (1) is independently 0.1 mol / L to 1 mol / L.
5. The method according to claim 3, characterized in that: The feed rate of the aqueous solution prepared with phosphoric acid is 30L / h to 90L / h.
6. The method according to claim 3, characterized in that The feed rate of the aqueous solution prepared with the magnesium salt is 10L / h to 30L / h.
7. The method according to claim 3, characterized in that The feed rate of the aqueous solution prepared by the zirconium salt is 10L / h to 30L / h.
8. The method according to claim 3, characterized in that The feed rate of the aqueous solution prepared by the titanium salt is 50L / h to 200L / h.
9. The method according to claim 2, characterized in that: The mass concentration of the ammonia solution is 15% to 30%.
10. The method according to claim 2, characterized in that The feed rate of the ammonia solution is 5L / h to 30L / h.
11. The method according to claim 2, characterized in that The time of the parallel addition is 1 h to 15 h.
12. The method according to claim 2, characterized in that: The positive electrode material precursor is a layered oxide positive electrode material.
13. The method according to claim 12, characterized in that The positive electrode material precursor is a quaternary layered oxide positive electrode material.
14. The method according to claim 2, characterized in that The reaction system containing the cathode material precursor is a reaction system for preparing the cathode material precursor by coprecipitation.
15. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material is prepared using the sodium ion battery positive electrode material precursor according to claim 1, and the sodium ion battery positive electrode material comprises a positive electrode material core and a NASICON type material coated on the surface of the positive electrode material core.
16. The sodium ion battery positive electrode material according to claim 15, characterized in that: Taking the total mass of the sodium ion battery positive electrode material as 100%, the mass content of the NASICON type material is 1% to 10%.
17. A method for preparing a positive electrode material for a sodium ion battery as claimed in claim 15 or 16, characterized in that: The method comprises the following steps: The sodium ion battery positive electrode material precursor and a sodium source are mixed and calcined to obtain the sodium ion battery positive electrode material.
18. The method according to claim 17, characterized in that The calcination temperature is 800°C to 1000°C.
19. The method according to claim 17, characterized in that The calcination time is 12h to 20h.
20. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material according to claim 15 or 16.
Citation Information
Patent Citations
Composite positive electrode material, preparation method and application thereof, sodium ion battery, sodium ion battery pack and equipment
CN114824269A
Sodium ion battery, positive electrode material and precursor thereof, and preparation method of positive electrode material and precursor
CN116375111A